Clinical Severity of Patients with COVID-19 Presenting to Nepal Armed Police Force Hospital: A Descriptive Cross-sectional Study (One Health Journal of Nepal, 2022)
Introduction: Coronavirus Disease 2019 (COVID-19), since its emergence, has spread rapidly as a pandemic causing massive loss of human life. This study aims to describe clinical severity of the disease in relation to age, mode of oxygen delivery and clinical outcome of patients admitted to a tertiary care center in Nepal.Methods: This was a descriptive cross-sectional study of data records of 130 COVID-19 patients 18 years and above admitted in Nepal Armed Police Force Hospital from April 2021 to June 2021 with Severe Acute Respiratory syndrome SARS-CoV-2 Reverse Transcriptase Polymerase Chain Reaction positive status. Ethical approval was obtained from Nepal Health research Council. Data were collected using structured proforma and analyzed using SPSS version 23.  Results: Patients with severe illness (52/130) constituted 40% of the bulk of COVID-19 patients, 48 of them requiring intensive care. Among them, 38.5% required non-invasive ventilation and 32.7% were intubated during treatment. Severity of illness was variable among different age groups but mortality was high among severely ill patients, 19/52 (36.5%) and with increasing age. The overall mortality was 19/130 (14%) over the study period, all of which were among severely ill patients.Conclusions: Most of the clinically severe cases required Intensive Care Unit admission, the majority receiving oxygen therapy via non-invasive or invasive mechanical ventilation, with a high mortality rate. The number of severely ill COVID-19 patients was variable in different age groups. Mortality, however, was observed in severely ill patients only and proportionately increased in COVID-19 patients with advancing age.